Microfacies, diagenesis, and stable isotope analysis of the Jurassic Jumara Dome carbonates, Kachchh, Western India: Implications for depositional environments and reservoir quality. (27th February 2019) - Khan, Zuhi; Sachan, Himanshu K.; Ahmad, A.H.M.; Ghaznavi, Asma A.
Abstract : The microfacies, detailed diagenesis, and stable isotope analysis of the carbonates, exposed at Jumara Dome, have been analysed to explore their impact on reservoir quality. The carbonates of Jumara Dome are mostly fine‐ to medium‐grained, and some are coarse‐grained, poorly to very well sorted, having angular to well‐rounded grains of low to high sphericity. Bioclasts are the most abundant constituent in these carbonates and includes brachiopods, foraminifers, ostracodes, calcispheres, algae, bryozoans, echinoderms, sponges, gastropods, and corals. Twelve microfacies were recorded in the present investigation. The temporal distribution of microfacies association reflects an ideal shallowing‐upward sequence representing a system of bioclastic bars developed on a carbonate ramp, which separates a lagoonal environment from open marine environment. In Jumara Dome carbonates, the δ 13 C values range from −1.89‰ to 1.44‰ and δ 18 O values range from −8.95‰ to −4.26‰ and suggest a marine environment of deposition for these carbonates under warmer Jurassic climate conditions. Micritization, silicification, compaction, cementation, neomorphism, geopetal structures, and porosity are the main diagenetic features affecting the carbonates and developed in marine phreatic, fresh water phreatic, mixed marine‐fresh water phreatic, and burial diagenetic environments. The diagenetic processes (mechanical compaction and cementation) has affected the carbonates reservoir characteristics, but the dissolution has resulted in generation of secondary porosity in the form of moulds, stylolites by pressure solution, and fractures (calcite veins), and enhancing the permeability resulting in improvement of carbonate reservoir characteristics, suggesting the carbonates of the Jumara Dome could be a better carbonate reservoir for petroleum accumulation.